Still in Another Castle: Asking New Questions about Games, Teaching and Learning - Staaby, Tobias (Gamevironments, 2021)
Research on digital game-based learning has mainly been concerned with exploring questions related to a core set of assumptions: that games, in a general sense, are effective learning tools by virtue of being motivating, engaging, adaptive and allowing for consequence-free failure and playful learning. This article revisits these assumptions and their associated questions in two levels: by subjecting them to parts of the Digital Game-Based Learning-literature problematizing these assumptions, and by contrasting them with a case-study conducted on teachers’ use of, and pedagogical reasoning for, using a commercial entertainment game in a course on ethics. The resulting discussion can be summed up in three main points: 1) that the arguments of game’s effectiveness relating to motivation, engagement, adaptivity and graceful failure should be reconsidered, and in some cases even dismissed, 2) pedagogical tools cannot easily be studied separately from their surrounding context, as implementation of a classroom element can result in widely different learning environments, and 3) if research on Digital Game-Based Learning aims to advance the field of game-based educational practice, then this requires a new set of questions to be asked, giving attention to the situated configurations of games and game elements, teachers, students, curricula and learning goals.